PENGELOLAAN WAKAF PRODUKTIF DALAM BENTUK SPBU STUDI KASUS SPBU MASJID AGUNG SEMARANG - Usman, Nurodin (Muqtasid: Jurnal Ekonomi dan Perbankan Syariah, 2013)
There are several variants of the management and development models that incorporate the concept of waqf productive and consumptive waqf. In the form of management and development of productive waqf property is manifested in the form of public refueling station (SPBU). This research is a descriptive qualitative study aimed to describe the management and development of waqf property of the Great Mosque of Semarang, which has an area of 119.1270 hectares of waqf land, particularly those managed to SPBU. The results showed that SPBU of Great Mosque of Semarang has succeeded in realizing the asset management model and the development of the productive waqf. SPBU of Great Mosque of Semarang have managed to make a significant contribution to the Great Mosque of Semarang and able to provide good service for consumers, as it provides the fuel needed by motorists generally. SPBU of Great Mosque of Semarang is also equipped with various facilities, such as prayer rooms, toilets, filling water and aeration, ATM, rest area, minimarket, clinic, car washbusiness